2000
DOI: 10.1143/jjap.39.5953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaCN2 Addition on the Densification Behavior and Electric Properties of AlN Ceramics

Abstract: Calcium cyanamide (CaCN2) has been used as a sintering aid as well as a dopant for AlN. The effect of CaCN2 addition on the densification behavior and electric properties of liquid-phase sintered AlN ceramics was investigated by X-ray diffraction (XRD), transmission electron microscopy (TEM) and scanning electron microscopy (SEM), dielectric and electric resistance measurements. Dense sintered specimens (relative density > 97.0%) were obtained using 1.0 to 2.0 wt% CaCN2 additives. With 0.5 to 3.0 wt% added … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In order to investigate the synthetic process of Ca 0.97 AlSiN 3 :Eu 0.03 2+ phosphors by the two‐step calcination procedure, XRD patterns of sample A, which was prepared using CaCN 2 , Si 3 N 4 and AlN at 1000°C for 2 h in nitrogen atmosphere, are shown in Figure . The diffraction peaks of Ca 3 N 2 and carbon indicated that CaCN 2 decomposed into calcium and carbon, leading to the nitridation of calcium in nitrogen atmosphere as shown in equation . 3CaCN2+Si3N4+AlN+N2Ca3N2()s+3C()s+2N2()g+Si3N4()s+AlN()s …”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the synthetic process of Ca 0.97 AlSiN 3 :Eu 0.03 2+ phosphors by the two‐step calcination procedure, XRD patterns of sample A, which was prepared using CaCN 2 , Si 3 N 4 and AlN at 1000°C for 2 h in nitrogen atmosphere, are shown in Figure . The diffraction peaks of Ca 3 N 2 and carbon indicated that CaCN 2 decomposed into calcium and carbon, leading to the nitridation of calcium in nitrogen atmosphere as shown in equation . 3CaCN2+Si3N4+AlN+N2Ca3N2()s+3C()s+2N2()g+Si3N4()s+AlN()s …”
Section: Resultsmentioning
confidence: 99%
“…Like most advanced ceramics, AlN does not occur naturally, synthesis of pure AlN is arduous due to its low chemical stability and it is difficult to sinter AlN to full density due to its covalent bonding. There exists oxygen on the grain boundaries and in the AlN lattice, which is responsible for the scattering of the primary heat carrier [4][5]; therefore, rare earth oxides and/or alkaline earth oxides are often added as sintering aids in the fabrication of AlN ceramics. These sintering aids not only contribute to form the liquid phase that promotes the densification by the process of liquid-phase sintering but also improve the thermal conductivity by decreasing the oxygen impurities in the AlN lattice [6][7].…”
Section: Introductionmentioning
confidence: 99%